2021
DOI: 10.1097/sle.0000000000001029
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility and Potential Advantages of Laparoscopic Management of Incarcerated Obturator Hernia Over the Open Approach

Abstract: The purpose of this study was to explore the feasibility and potential advantages of laparoscopic surgery in the treatment of incarcerated obturator hernia (IOH).Materials and Methods: Clinical data of 23 patients with IOH who underwent emergency surgery at our hospital from June 2015 to October 2020 were retrospectively analyzed. The clinical characteristics and surgery outcomes were compared between the laparoscopic group, open group, and the previously published data.Results: Twelve patients with IOH were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Interestingly, obturator hernias are twice as commonly observed on the right side [ 15 ]. This asymmetry is attributed to the anatomical location of the sigmoid colon, which predominantly occupies the left side of the pelvis which may lead to increased pressure and vulnerability on the right side, predisposing individuals to herniation in that specific area [ 5 , 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, obturator hernias are twice as commonly observed on the right side [ 15 ]. This asymmetry is attributed to the anatomical location of the sigmoid colon, which predominantly occupies the left side of the pelvis which may lead to increased pressure and vulnerability on the right side, predisposing individuals to herniation in that specific area [ 5 , 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, laparoscopic repair has some advantages over open procedures. It has been associated with less bleeding, a shorter postoperative length of stay, and fewer postoperative complications compared with an open approach [ 7 , 15 , 26 ]. Specifically, one study by Schizas et al [ 5 ] demonstrated that laparoscopic repair was associated with a significantly reduced postoperative morbidity rate, with less than 10% of cases requiring conversion to laparotomy.…”
Section: Discussionmentioning
confidence: 99%